PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT LUCKY INDAH KERAMIK KOTA TANGERANG - Fauziyah, Syifa; Hindriari, Reni (Journal of Research and Publication Innovation, 2024)
This study aims to determine the partial and simultaneous influence of Work Discipline (XI) and Work Environment (X2) on Employee Performance (Y) at PT Lucky Indah Keramik Kota Tangerang. The method used is a quantitative method. The object of this study is the employees of PT Lucky Indah Keramik Tangerang City. The sample in this study amounted to 60 employees. Data analysis and test techniques include validity tests and reliability tests, classical assumption tests, simple and multiple linear regression tests, correlation coefficient tests, determination coefficient tests and hypothesis tests using the Statistical Package for the Social Science (SPSS) Version 26. The result of this study is that Work Discipline partially has a positive effect on Employee Performance, this is evidenced by the results of the hypothesis test obtained t calculation > t table or 6.008 > 2.001 with a significance value of 0.000 > 0.5. The Work Environment partially has a positive effect on Employee Performance, this is evidenced by the results of the hypothesis test obtained t calculation > t table or 4.806 > 2.001 with a significance value of 0.000 > 0.5. Discipline and Work Environment simultaneously had a positive and significant effect on Employee Kineria with the results of the hypothesis test obtained F count > F table or 24.923 > 3.16 with a significance value of 0.000 > 0.005. The magnitude of the influence of Work Discipline (X₁) and Work Environment (X₂) on Employee Performance (Y) at PT Lucky Indah Keramik Kota Tangerang is 68.3% and the remaining 31.7% is influenced by other factors.